Does Lung Donation by Heart Donors Have an Impact on Survival in Heart Transplant Recipients?. Issue 2 (25th August 2016) - Xia, Y.; Friedmann, P.; Bello, R.; Goldstein, D.; D'Alessandro, D.
Abstract : Lung procurement is increasing during multiorgan recovery and substantially alters the explant process. This study evaluated whether lung donation by a heart donor affects survival in heart transplant recipients. Retrospective analysis of United Network for Organ Sharing (UNOS) adult heart transplantation data from 1998 to 2012 was performed. Lung donors (LDs) were defined as those having at least one lung procured and transplanted. Non‐LDs had neither lung transplanted. Heart transplant recipients who had previous transplants, who had heterotopic transplants, who were waitlisted for other organs or who were temporarily delisted were excluded from the analysis. Kaplan–Meier survival analysis and Cox proportional hazards regression were performed. Of 23 590 heart transplant recipients meeting criteria during the study period, 8638 (36.6%) transplants were from LDs. Donors in the LD group had less history of cigarette use (15.5% vs. 29.5%, p < 0.001). On univariate analysis, LDs were associated with improved patient survival (p < 0.001). On multivariate analysis, LDs were not significantly associated with patient survival (adjusted hazard ratio 0.98, 95% confidence interval 0.94–1.03). Analysis of the UNOS registry suggested that donor pulmonary status and lung procurement had no detrimental effect on survival in heart transplant recipients, supporting the present practice of using donor lungs whenever possible. Abstract : Multivariate Cox proportional hazards regression of data from the United Network for Organ Sharing registry finds that lung donation by heart donors does not have an impact on survival in heart transplant recipients.